Too much of a good thing: Overproduction of virulence factors impairs cryptococcal pathogenicity - Reuwsaat, Julia C. V. (Microb Cell, 2021)
The regulation of virulence factor production and deployment is crucial for the establishment of microbial infection and subsequent pathogenesis. If these processes are not properly coordinated, the infecting pathogen is less likely to both survive the immune response and cause damage to the host. One key virulence factor of the opportunistic fungal pathogen Cryptococcus neoformans, which kills almost 200,000 people each year worldwide, is a polysaccharide capsule that surrounds the cell wall; this structure helps the fungal cells resist engulfment and elimination by host phagocytes. Another important virulence trait is the development of a giant (Titan) cell morphotype that increases fungal resistance to phagocytosis, oxidative stress, and antifungal treatment. We recently identified the transcription factor Pdr802 as essential for C. neoformans adaptation to and survival under host conditions both in vitro and in vivo (Reuwsaat et al., mBio, doi: 10.1128/mBio.03457-20). Cryptococci lacking Pdr802 display enlarged capsules and enhanced Titan cell production, along with dramatically reduced virulence in a mouse model of infection. These results demonstrate that more is not necessarily better when it comes to virulence factors. Instead, precise regulation of these traits, to avoid both under- and overexpression, is critical for the success of this pathogen as it faces the challenges imposed by the host environment.